« Le conservatoire, c’est une chance ! » - Natacha Gourland (EchoGéo)
This article proposes to analyze twelve dance conservatories in the inner suburbs of Paris as spaces of parenthood. The use of these cultural facilities makes them spaces of social distinction, where different power relationships are played out and where singular spatial tactics are deployed. The parents who enroll their children, and in particular their daughters, seek to supervise their offspring and transmit codes of good conduct designed to integrate them into society. At the interface of educational and recreational functions, dance conservatories are therefore artistic devices targeted by parents, where strategies of respectability are articulated.